Friend or foe: reconciliation between males and females in wild chacma baboons. (May 2019) - Webb, Christine E.; Baniel, Alice; Cowlishaw, Guy; Huchard, Elise
Abstract : Male aggression towards females is a common and often costly occurrence in species that live in bisexual groups. But preferential heterosexual relationships are also known to confer numerous fitness advantages to both sexes—making it of interest to explore how aggression is managed among male–female dyads through strategies like reconciliation (i.e. postconflict affiliative reunions between former opponents). In this study, we build on the traditional postconflict matched-control (PC-MC), time rule and rate methods to validate a novel methodological approach that tests for the presence and form of reconciliation between male and female wild chacma baboons, Papio ursinus . We show that heterosexual opponents exhibit friendly postconflict reunions, further demonstrating that reconciliation occurs almost exclusively between males and pregnant/lactating females who form tight social bonds. Such 'friendships' represent stable associations offering proximate and ultimate benefits to both parties—mainly improving (future) offspring survival. This aligns our findings with the 'valuable relationship hypothesis', which predicts rates of reconciliation to increase with the fitness consequences of the opponents' bond. Moreover, patterns concerning the initiative to reconcile reveal that males are as likely as females to initiate reconciliation, suggesting that males play a heretofore underappreciated role in maintaining heterosexual friendships. Beyond proposing a multivariate methodological technique applicable to other long-term observational data sets, the present research illuminates how male–female aggression in promiscuous societies may be mitigated via relationship repair strategies like reconciliation, the balance in those efforts between partners shedding new light on the mutual investment in such bonds. Highlights: Heterosexual opponents reconcile after aggression in a promiscuous primate society. Friends but not nonfriends reconcile, backing the valuable relationship hypothesis. Males and their female friends are equally likely to initiate reconciliation. Males may play an underappreciated role in maintaining heterosexual friendships. We present a novel method to study reconciliation using observational data sets.